A simple and rapid LC–MS/MS method for quantitation of luseogliflozin in rat plasma and its application to a PK study. (January 2017) - Kobuchi, Shinji; Matsuno, Megumi; Kawamoto, Momoko; Kojima, Naoto; Ito, Yukako; Yamashita, Masayuki; Sakaeda, Toshiyuki
Aim: Luseogliflozin is a novel sodium-dependent glucose cotransporter-2 inhibitor for the treatment of Type 2 diabetes mellitus. To assist pharmacokinetic and toxicodynamic studies, a rapid LC–MS/MS method were developed and validated for the quantitation of luseogliflozin in rat plasma.Results: Sample preparation was carried out using simplified protein precipitation and liquid–liquid extraction procedures, and the run time was only 4 min. Extraction recovery was 92.9 to 95.3%, and the method was validated over the range 0.5 to 500 ng/ml for luseogliflozin with acceptable specificity, accuracy and precision.Conclusion: The validated method is considered suitable to quantify luseogliflozin in pharmacokinetic and pharmacodynamic/toxicodynamic studies in rats.